CAN ENGLISH VOCABULARY ACQUISITION OF A YOUNG LEARNER BE CATALYZED BY EDUCATIONAL VIDEOS? - Hasanah, Eni Uswatun; Rusmawaty, Desy; Jany Kalukar, Ventje (Berumpun: International Journal of Social, Politics, and Humanities, 2024)
This study explores the effectiveness of educational videos in facilitating English vocabulary acquisition in a young learner. The research employs a qualitative case study approach, focusing on a 4-year-old girl exposed to educational videos. Data was collected through observations, recordings, and interviews, emphasizing the acquisition of basic vocabulary such as colors, animals, and numbers. The findings reveal that educational videos significantly aid vocabulary learning by providing engaging visual and auditory stimuli. However, the study underscores the importance of human interaction in language acquisition, suggesting that while educational videos are a valuable tool, they should complement traditional learning methods rather than replace them. This research offers insights for educators and parents on integrating multimedia resources into early language learning strategies.